PERANCANGAN APLIKASI GAME VIRTUAL REALITY CERITA RAKYAT RAMAYANA MENGGUNAKAN PLATFORM ANDROID - Putu Bagus Satria Paramartha; I Made Arsa Suyadnya; Made Sudarma (Jurnal SPEKTRUM, 2020)
Indonesia is the largest archipelago country in the world that has a variety of folklore from allparts of Indonesia. One of the most famous folklore in Indonesia is the Ramayana story. In thismodern era, people's interest in folklore, especially the younger generation is very alarming. This isbecause the background of the story and the characters in most folklore are considered outdated andno longer relevant to today's life. Based on this problem, the virtual reality game application of theRamayana folklore was made to visualize the Ramayana folklore in a more interesting and dynamicway in order to increase the interest of the community to be more fond of Indonesian folklore.Application development starts from the concept, design, material collection, assembly, testing, anddistribution stages. This application was built using C # programming language, Google CardboardSDK, Blender and Unity software. The results obtained are an application that can be used as amedium of entertainment or learning about Ramayana folklore. In this Ramayana folklore gameapplication, users can play 3 stage games that are equipped with game narratives consisting of textand images. Based on the test results using the Black-Box method, the functional application hasbeen able to run as it should. Based on testing the System Usability Scale (SUS), this applicationobtained an average value of 20 respondents at 73.13 with C of SUS’s Grade Scale, which isAcceptable category.